Implementasi Manajemen Risiko pada Sistem Asuransi Jiwa Syariah Di PT. Prudential Life Asurance Binjai - Risma Dani A.; Yusrizal Yusrizal (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
AbstractThis article discusses risk management in Islamic insurance companies. Sharia insurance in general is not much different from traditional insurance. In insurance, there are similarities between the perspective of Islamic sharia and conventional insurance, namely that the insurance company is only an intermediary in the structural relationship between the premium payer (insurer) and the claimant (insured) and determines how the risk should be managed. Recognizing company problems and, where possible, minimizing risks creates efficiency and effectiveness, which ultimately contributes to achieving company goals and facilitating them. It can take the form of operational risks such as bankruptcy, legal risks and reputation risks. In addition, a decrease in morale also often occurs, because the constraints faced by the company come from external and internal companies.keywords: sharia insurance, risk management, Prudential Life Assurance Binjai.